"Person and act" and related essays - John Paul II, Pope, 1920-2005 (The English critical edition of the works of Karol Wojtyła/John Paul II ;, 2021)
"A new translation, with scholarly notes and textual annotations based on new research into archival collections, of Wojtyla's most well-known philosophical work and related fragments, addresses, and letters"--